2007
DOI: 10.1007/s10827-007-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

Transition between two excitabilities in mesencephalic V neurons

Abstract: Neurons can make different responses to identical inputs. According to the emerging frequency of repetitive firing, neurons are classified into two types: type 1 and type 2 excitability. Though in mathematical simulations, minor modifications of parameters describing ionic currents can result in transitions between these two excitabilities, empirical evidence to support these theoretical possibilities is scarce. Here we report a joint theoretical and experimental study to test the hypothesis that changes in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We also suggested that this channel density paradigm may explain the different threshold dynamics of regular and fast spiking cortical neurons [2], [7], [8], as well as that of Class 1 and Class 2 axons in Carcinus maenas [1]. The physiological and pharmacological relevance of channel densities as bifurcation variable has recently been experimentally confirmed [37], [38].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We also suggested that this channel density paradigm may explain the different threshold dynamics of regular and fast spiking cortical neurons [2], [7], [8], as well as that of Class 1 and Class 2 axons in Carcinus maenas [1]. The physiological and pharmacological relevance of channel densities as bifurcation variable has recently been experimentally confirmed [37], [38].…”
Section: Discussionmentioning
confidence: 75%
“…Such flexibility has also been shown in cortical fast spiking (Type 2) interneurons [45]; Type 2 dynamics being changed to Type 1 dynamics when the K channel density (in soma) is reduced in dynamic clamp experiments. Similarly, fast spiking mesenchaplic V neurons have been shown to belong to the M1/2 class [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study it was shown that ASR only appears obviously in the neurons with higher frequency resonance, suggesting that the intrinsic property of resonance is a decisive factor for occurring ASR behavior in neurons. This kind of neurons should belong to class 2 excitability which exhibits subthreshold oscillations before the occurrence of spikes and fires at a higher rate, though the rate is relatively independent of the strength of stimulation current [15,16,[29][30][31] . In another word, at least in sensory neurons, only the neurons with class 2 excitability could exhibit ASR behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Of these three types of neurons, class 2 neurons, which are similar to the rhythmical burst neurons mentioned above, have received excessive attention [26,28,30]. With the help of nonlinear dynamics theory, these three classifications are described to have different dynamic bifurcation mechanisms [72]. …”
Section: Neuronal Excitability Classification and Excitability Transimentioning
confidence: 99%
“…In an interesting study on the chronic compression of rat sciatic nerves, it was shown that at a bifurcation point of critical sensitivity, patterns of bursting in an experimental pacemaker can be altered when the extracellular calcium concentration is changed [12,73,74]. For Mes V neurons, a theoretical study using mathematical models has demonstrated that small changes in the parameters related to ionic currents could lead to transitions between different classes of membrane excitability [72]. Different dynamic properties of ionic currents which were detected in different types of Mes V neurons provide experimental support for this possibility.…”
Section: Neuronal Excitability Classification and Excitability Transimentioning
confidence: 99%